Systematic review of modern techniques in qualitative research - Vivek, Ramakrishnan (Management and Entrepreneurship: Trends of Development, 2022)
According to Mayan (2009), being a qualitative researcher entails various activities “It is a pleasure to share life and learning with others to make sense of our reality jointly. Non-experimental qualitative research is not only conducted with people but also performed through people.” According to its many definitions, qualitative research entails significant interpersonal contact. Throughout the process of qualitative research, from strategy to implementation, effective communication is essential. While numerous new qualitative research tools have emerged over the last several decades, those linked to communication technology have emerged as the most important and impactful. Because there is little information available regarding communication technologies in qualitative research, this article aims to produce an overview of the new developing technologies currently being used. For that, the writer has reviewed several pieces of literature on qualitative research. As surfaced from the literature, qualitative research has transformed to new heights using modern techniques. Therefore, qualitative researchers must keep up to date with the latest technological advances to get maximum productivity.JEL Classification: А10, А12.